The Use of Areca Nut Fiber in Soundproof Particle Board Manufacturing. - Zulkarnain, Anis Syahirah; Shahruddin, Aida Fatiha; Aspawani, Nurbaiduri Batrisyia; Aslila Abd Kadir (Multidisciplinary Applied Research and Innovation, 2023)
Areca is one type of plant which has many used. The seed and stem have been utilized while the shell coin only becomes organic waste. The aim of this project is to produce particle board form areca fiber as a soundproof panel. The urea-formaldehyde glue and hardener will be combined during the production of this particle board made from areca fiber. Studies show that areca has the potential to be utilized in particle board construction since natural fiber is an excellent sound absorber. This research will take place in UTHM Pagoh's laboratory. Particle boards with thickness of 5mm and 10mm with size of 300mm x 300mm have been fabricated going through mechanical and physical tests. Mechanical tests like the MOR test and the water absorption test are produced. The MOR values found were 6.75 mg/mm2 and 2.81mg/mm2. while the water absorption test is 200.0% and 191.7%. As a sound absorbing particle board, through the sound absorption test it is found that the transmission loss value is 10.3dB and 15.4dB. Lastly, particle board form areca fiber can be used as a soundproof panel in the construction industry.